Genetic and Morphological Evidence to Split the Coris julis Species Complex (Teleostei: Labridae) Into Two Sibling Species: Resurrection of Coris melanura (Lowe, 1839) Redescription of Coris julis (Linnaeus, 1758) - Ramírez-Amaro, Sergio; Ordines, Francesc; Fricke, Ronald; Ruiz-Jarabo, Ignacio; Bolado, Ignacio; Massutí, Enric (Frontiers in Marine Science, 2021)
The genus Coris contains 28 valid species, most of them with an Indo-Pacific distribution and only two species recognized from the eastern Atlantic: Coris atlantica and C. julis. This last species has a large variability in its coloration, which caused that during the first half of XIX century the sexes were considered as different species. Two liveries have been described for C. julis: i) primary or “giofredi”, which corresponds to females and primary-phase males and is considered common for Atlantic and Mediterranean populations; and ii) the secondary or “julis” which corresponds to terminal-phase males, which is different for Atlantic and Mediterranean populations. In this study we demonstrate the existence of two sibling species within the C. julis species complex. Morphological and molecular analyses showed that this species complex is composed of two species: i) C. julis, distributed mainly in the Mediterranean, from which the species was originally described; and ii) C. melanura, a species described by Lowe in 1839 which is resurrected here, mainly distributed in the eastern Atlantic and western Mediterranean. We also discuss the possible phylogeographic events to understand the contemporary distribution patterns of Coris species in the eastern Atlantic and Mediterranean.